Buddhist Economic: For Student Creativity Program in Entrepreneurship by Catera Zebuart Product - Tata Ananta Nur Juwarso; Dwi Sagitha Febrianti; Misdayanti; Sulaiman (GoAcademica Research & Publishing, 2022)
Several sources of primary Buddhist scriptures, secondary literature, and scientific articles were examined to find out what economic system was derived from the teachings of Buddhism described by Gautama Buddha. The principles of Buddhist economics are investigated from the personal and social ethics of the Buddhists that underlie the system. An economic system that adheres to Buddhist moral norms, and attitudes towards property and wealth that inspire in economic endeavors in particular entrepreneurial behavior. The method used is systematic content analysis. Entrepreneurship based on Buddhist values ​​is also analyzed to be applied in the Student Creativity program in the field of Entrepreneurship. Generosity which is the principle of Buddhist economics in this study is also applied. Through an institution approved by the Directorate General of Buddhist Community Guidance together with the Directorate of Taxes, the Ministry of Finance, six formal institutions similar to the Amil Zakat Agency in Islamic Religious Institutions were obtained. Meanwhile, the selected product is based on the creative economy in the form of a conscious work of art called Catera Zebuart.